Electromechanical instability in silicone‐ and acrylate‐based dielectric elastomers. Issue 9 (26th October 2017) - Jiang, Liang; Zhou, Yanfen; Chen, Shaojuan; Ma, Jianwei; Betts, Anthony; Jerrams, Stephen
ABSTRACT: Electromechanical instability (EMI) is regarded as a significant factor in preventing dielectric elastomers (DEs) from achieving large voltage‐induced deformations. In this study, the strain‐stiffening effect was used to control the occurrence of EMI in DEs. The results show that the stretching ratio required to provide a feasible strain‐stiffening effect in silicone rubber (SR) was smaller than that needed for a commercial DE material, VHB 4910. The experimental data were compared with currently used models for the simulation of EMI in DEs. We found that EMI could be eliminated in the deformation of these elastomers when prestretching was used. Through the application of a prestretching ratio of above 2.0, EMI was suppressed in both the VHB 4910 and SR samples. The findings of this research are of great significance in the maximization of the electromechanical performance of DE materials. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45733. Abstract :